Adaptasi Sosial Gay Muslim Indonesia Terhadap Agama dan Keluarga The social adaptation of Gay Muslim to Religion and Family - Adihartono , Wisnu (Jurnal Masyarakat dan Budaya, 2025)
The LGBT groups in Indonesia have little or no power and limited access to fight for their rights. Growing up in a system where one cannot be or say who they truly are, places them in a position where they are in a constant state of having to negotiate life within a hostile environment. This paper will look their (social) adaptation between their religion (Islam) and their family. They have to obey their religion, as well as they also have to obey and respect to their family in order to preserve the family’s honor. Those complexities raise a hierarchy, which is side by side with the religious teachings, culture and norms that causes a difficulty for them to come out showing as a gay. For this paper, I took the data from my doctoral research at Ecole des Hautes Etudes en Sciences Sociales (EHESS), France which I completed in 2015. For the purposes of this paper, I only used ten questions that are very closely related to religious and family issues.